Transport et interaction matière–rayonnement dans des matériaux corrélés - Feuillet-Palma, Cheryl (Comptes Rendus. Physique)
Matter–radiation interaction can both probe the physics of these complex systems and generate new functionalities in low-dimensional quantum devices. This review is a synthesis of research carried out around the study of strongly correlated materials, in particular oxide interfaces LaAlO3/SrTiO3 and two families of cuprates YBa2Cu3O7-𝛿 and Bi2Sr2CaCu2O8+𝛿.